Strength efficiency evaluation of cemented tailings backfill with different stratified structures. (1st February 2019) - Xu, Wenbin; Cao, Yang; Liu, Binghua
Highlights: The stratified structure has a positive or negative effect on the strength of CTB. The UCS development of stratified CTB shows a V-type distribution. The stratified CTB specimens show significant brittle characteristic. Abstract: This paper presents the results of an experimental research on the mechanical performance and failure pattern of stratified cemented tailings backfill (CTB). Different stratified CTB samples with various cement/tailings ratios (1/4, 1/8, 1/10), solid concentrations (72 wt%, 75%, 78%) are prepared and cured in a well controlled chamber with temperature at 20 °C and 90% ± 5% relative humidity. Mechanical tests are conducted on the samples, in which the scanning electrical microscopic (SEM) and thermal gravity (TG) analysis of stratified CTB specimens are performed. The results show that the binder content, solid content and curing age enhance the uniaxial compressive strength (UCS) of stratified CTB. The stratified structure can have an effect on the compressive strength of CTB, depending on the backfilling ratio at a time (each filling height at a time to the total filling height is defined as the backfilling ratio), i.e., a comparatively large backfill ratio at a time has a negative effect on the strength of stratified CTB. However, a small backfilling ratio lead to strength increase at all ages and magnitude of the positive effect is increased with the decreases in the backfilling ratio at a time. The UCS development of stratified CTB with backfilling ratio follows a similar trend that first reduces to a lowest value, and then gradually increases regardless of binder content and solid concentration. When the binder content and curing age are constant, there is a good polynomial relationship between the stratified coefficient of CTB specimen and backfilling ratio. The failure patterns of stratified CTB samples contain tensile, shear and hybrid failure pattern. The stratified CTB specimen with 50% and 25% backfilling ratio are characterized by conjugate tensile failure and shear failure pattern, and the stratified CTB specimens with backfilling ratio of 12.5 and 10% are mainly shear failure pattern. The results also show that a good understanding of the effect of stratified structure on the compressive strength of CTB is crucial for designing reasonable CTB structure with high mechanical property, reducing the backfilling operations cost.